Sensory axon-derived neuregulin-1 is required for axoglial signaling and normal sensory function but not for long-term axon maintenance. - Fricker, F; Zhu, N; Tsantoulas, C; Abrahamsen, B; Nassar, M; Thakur, M; Garratt, A; Birchmeier, C; McMahon, S; Wood, J; Bennett, D (2009)
Neuregulin-1 has a key role in mediating signaling between axons and Schwann cells during development. A limitation to studying its role in adulthood is the embryonic lethality of global Nrg1 gene deletion. We used the Cre-loxP system to generate transgenic mice in which neuregulin-1 is conditionally ablated in the majority of small-diameter and a proportion of large-diameter sensory neurons that have axons conducting in the C- and Adelta-fiber range, respectively. Sensory neuron-specific neuregulin-1 ablation resulted in abnormally large Remak bundles with axons clustered in "polyaxonal" pockets. The total number of axons in the sural nerve was unchanged, but a greater proportion was unmyelinated. In addition, we observed large-diameter axons that were in a 1:1 relationship with Schwann cells, surrounded by a basal lamina but not myelinated. There was no evidence of DRG or Schwann cell death; the markers of different DRG cell populations and cutaneous innervation were unchanged. These anatomical changes were reflected in a slowing of conduction velocity at the lower end of the A-fiber conduction velocity range and a new population of more rapidly conducting C-fibers that are likely to represent large-diameter axons that have failed to myelinate. Conditional neuregulin-1 ablation resulted in a reduced sensitivity to noxious mechanical stimuli. These findings emphasize the importance of neuregulin-1 in mediating the signaling between axons and both myelinating and nonmyelinating Schwann cells required for normal sensory function. Sensory neuronal survival and axonal maintenance, however, are not dependent on axon-derived neuregulin-1 signaling in adulthood.